The needs of informal caregivers caring for stroke patients in the home environment - Bendová, Markéta; Vacková, Jitka; Míková, Marcela; Kuželková, Anna (Kontakt, 2024)
Background: Stroke is the leading cause of disability, impacting both the affected person and informal caregivers. As the number of stroke patients rises, it is increasingly important to recognize that informal stroke caregivers have needs that require support and interventions. Objectives: The aim was to create an overview of studies where informal caregivers express their specific needs related to providing care for stroke patients in the home environment and summarize the described needs into particular categories. Methods: A review of the literature published between 2013-2023 was conducted using the PRISMA methodology. The search for relevant articles used electronic databases Web of Science, Scopus, and PubMed. 21 articles met the entry criteria. Results: Our analysis revealed 10 domains of needs of informal caregivers taking care of stroke patients in the home environment: the need to obtain information, the need to learn the life aspects of the patient after stroke, the need for a new family dynamic, the need to manage practical matters/non-care tasks, the need to communicate with the patient, the need for closeness, the need for physical health, the need for mental health, social needs, and the need for formal and informal support. Conclusion: The burden on informal caregivers has been confirmed by a wealth of research, including this study. As challenges faced by stroke patients and their caregivers evolve, their needs must be regularly reviewed to ensure appropriate interventions, treatments, and support to improve overall care after a stroke.
Keywords: odhad potřeb; Needs Assessment; Home Nursing; Meta-Analysis as Topic; cévní mozková příhoda; osoby pečující o pacienty; metaanalýza jako téma; Stroke; lidé; Humans; domácí ošetřování; Caregivers